The role of post-systolic strain and electrocardiographic changes during dobutamine stress echocardiography in enhancing detection of symptomatic coronary artery disease - Zivanic, Aleksandra; Stankovic, Ivan; Vranic Jovanovic, Ivona; Panic, Milos; Scepanovic, Milica; Maksimovic, Aleksandra; Milicevic, Predrag; Kalezic-Radmili, Tijana; Neskovic, Aleksandar N. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTo enhance the diagnosis of coronary artery disease (CAD) during dobutamine stress echocardiography (DSE), subjective visual evaluation of left ventricular (LV) wall motion abnormalities may be complemented by analyzing myocardial deformation and electrocardiographic (ECG) changes.AimsThis study evaluates the post-systolic strain index (PSI) measured during the recovery phase of DSE for detecting obstructive CAD and explores its relationship with wall motion abnormalities and ECG changes during DSE in patients with anginal symptoms.MethodsWe retrospectively analyzed data from 72 patients who underwent both DSE and coronary angiography. We compared visual interpretation of DSE at peak stress, ECG abnormalities during DSE, and PSI during the recovery phase with obstructive CAD.ResultsLV wall motion abnormalities induced by dobutamine were independently associated with obstructive CAD [odds ratio (OR) 8.58, 95% confidence interval (CI) 2.67–27.50, p < 0.011], diagnosed in 44% of patients. Significant ECG changes during DSE correlated with obstructive CAD (OR 4.41, 95% CI 1.41–13.81, p = 0.011). PSI during recovery did not correlate with DSE-induced wall motion abnormalities (OR 1.45, 95% CI 0.49–4.24, p = 0.497) or obstructive CAD (OR 1.00, 95% CI 0.342–2.926, p = 1.00), but was associated with pathological ECG changes (OR 5.51, 95% CI 1.05–28.99, p = 0.044).ConclusionsPSI measured during the recovery phase of DSE is not associated with DSE-induced wall motion abnormalities and obstructive CAD in patients with anginal symptoms. However, PSI may be related to ECG changes and could potentially reflect subtle, stress-induced myocardial dysfunction, possibly involving coronary microvascular impairment.